The Role of the French Colonial Assimilation Project in Shaping the Algerian National Identity - الغامدى، حسنة بنت شويل أحمد (جامعة الملك عبدالعزيز, 2022)
تستعرض هذه الورقة التاريخية دراسة مشكلة الهوية في الجزائر الحديثة حيث تواجه الهوية في الجزائر تحديا خطيرا لنمو البلاد وتقدمها. ويخلص المقال إلى أن جذور هذا الاختلاف يمكن تحديدها في سياسة الاندماج التي تبنتها فرنسا أثناء استعمار الجزائر، فكان لهذه التجربة السياسية تأثير دائم على النخب الثقافية الجزائرية، كما شكلت بداية الصراع بين توجهين ثقافيين رئيسيين هما الفرانكفونية والقومية العربية. وفي هذه الورقة سيتم مناقشة وتحليل الحجج التاريخية لكل مجموعة وادعاءاتها بأنها أفضل ممثل للهوية، كما يتناول البحث دراسة النقاش الدائر حول التعريب في الجزائر بين المجموعتين. This paper returns to history to examine the problem of identity in modern Algeria. The identity crisis facing modern Algeria constitutes a grave challenge to the country's growth and progression. The article concludes that the root of this difference can be delineated in the policy of integration adopted by France during its colonisation of Algeria. This political experiment had a lasting effect on Algeria's cultural elites and marked the beginning of the conflict between its two mainstream cultural orientations the Francophone and Pan-Arab groups. The paper subjects to historical analysis the arguments of each group and their claims to being the best representative of the Algerian identity. It concludes the discussion by examining the ongoing debate of Arabisation in Algeria between the two groups.
Keywords: الاحتلال الفرنسي -- المقاومة الوطنية -- التاريخ الجزائري -- الثقافة الجزائرية -- الجزائر